Values of ultrasound for diagnosis and management of insulin-induced lipohypertrophy: A prospective cohort study in China. Issue 29 (23rd July 2021) - Wang, Wei; Huang, Rong; Chen, Yang; Tu, Mei
Abstract : Abstract: The aim of this study was to explore the values of ultrasound for diagnosis and management of insulin-induced lipohypertrophy and further analyzing the impact of body mass index and subcutaneous fat thickness on ultrasound manifestations of lipohypertrophy. In this 3-month, prospective cohort study, a total of 162 patients with diabetes who used insulin therapy more than 1 year with unknown lipohypertrophy status were enrolled into this study. Demographic information, assessment of glycemic control and insulin injection technique were evaluated. Physical and ultrasound examination were separately performed to detect lipohypertrophy by a team of diabetes educator nurses or ultrasonographer in a blinded fashion. Patients with lipohypertrophy received insulin injection technique education based on ultrasound examination and Chinese guideline. Ultrasound examination detected 41.1% more patients (74.1% vs 52.5%; P  < .001) with lipohypertrophy and 61.2% more lesions (216 vs 134; P  < .001) than physical examination. Glycosylated hemoglobin A1c and fasting blood glucose were significantly decreased in patients with lipohypertrophy or subclinical lipohypertrophy (lipohypertrophy without visual and palpation changes) after receiving insulin injection technique education based on ultrasound examination and Chinese guideline than baseline at 3 months ( P  < .001). The proportion of lesions with ultrasound manifestation 2 (distortion of surrounding connective tissue) in obese and STF (>15 mm) groups were no more than 50% and showed a decreased trend with increased subcutaneous fat thickness and body mass index ( P  < .001). Lipohypertrophy has characteristic ultrasound manifestations which can detect more accurate results than palpation alone and provide detailed information to promote effective education on lipohypertrophy management, thereby improving glycemic control.